Numerical analysis of the deep soil failure mechanism for perimeter pile groups - Watford, M; Templeman, J; Orazalin, Z; Zhou, H; Franza, A; Sheil, BB (ICE Publishing, 2021)
In this paper, the lateral limiting pressure offered by the deep ‘flow-around’ soil failure mechanism for perimeter (ring) pile groups in undrained soil is explored using two−dimensional finite element modelling. A parametric study investigates the role of group configuration, pile−soil adhesion, group size, pile spacing and load direction on group capacity and corresponding soil failure mechanisms. The finite element output show that the plan group configuration (square or circular) has a negligible influence on lateral capacity for closely spaced perimeter pile groups. When compared to ‘full’ square pile groups with the same number of piles, the present results suggest that for practical pile spacing (≳ two pile diameters), perimeter groups do not necessarily increase capacity efficiency, particularly if the piles are smooth. Nevertheless, perimeter groups are shown to be characterized by both the invariance of their capacity to the direction of loading and their highly uniform load sharing between piles, which are beneficial features to optimize design.